The significance of non-verbal behaviour in teacher-learner interaction in GFL classes - A. Daraghmi; R. Asali-van der Wal (Russian State Vocational Pedagogical University, 2023)
Introduction. Non-verbal communication (NVC) is the first language that adults encourage kids to acquire. It is one of the most important areas of study in educational institutions, as it is impossible for a teacher to convey information effectively without using non-verbal cues. When learning a foreign language, a person should be able to interact with others through both verbal and non-verbal cues.Aim. The present research aims to emphasise the importance of non-verbal behaviour in teacher-learner interaction in GFL classes and to analyse the various NVC methods and motivations that GFL teachers employ in classrooms.Methodology and research methods. Nine non-verbal communication-related statements were assessed by interviewing 34 GFL teachers teaching in Jordan, at the German-Jordanian University of Applied Sciences in Madaba, the University of Jordan and the Language Generation Centre in Amman.Results and scientific novelty. The study found that GFL teachers used non-verbal behaviour both consciously and unconsciously and considered eye contact an essential tool that can be used in class.Teachers regulated the course of their lesson with their posture and used their tone of voice as an important tool for ending classroom disruptions. Moreover, they used facial expressions and physical gestures to express and clarify their emotions, and they believed that non-verbal cues were crucial for effective teaching from both the teacher's and the learner's viewpoints. They also regarded proximity and distance as very important tool in teacher-learner interaction.Practical significance. By examining how NVC techniques are used in the classroom and their results from the teachers' perspective, the current study contributes to the body of knowledge previously accessible on NVC and foreign language training. This would provide a more practical understanding how to use these instruments outside of research. Teachers who have implemented these NVC techniques in their classrooms may be able to shed some light on the applicability of NVC in different settings that have not been covered in other research articles. This paper is a documentation of NVC techniques that German instructors use in their classes and are considered effective in class. It also discusses the many justifications for which teachers might employ NVC in the classroom. It provides an answer to the matter of whether teachers intentionally or unintentionally use NVC techniques in the classroom.